Wrist ganglions management:aspiration and autologus blood instillation - Qassim, Yasir N. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Ganglions are the most common benign cystic swellings found around the wrist,they can be treated conservatively or by surgical excision,but the net results revieled no significant difference.Complete evacuation of the cysts followed by intracystic autologus blood instillation has given encouraging results.Objective: To assess the efficacy and safety of aspiration of wrist ganglions and instillation of autologus blood inside the cysts.Patients and Methods: Aprospective study was conducted on forty patients with wrist ganglions.20% of the patients underwent aspiration of the cysts alone,and the other 20 underwent aspiration of the cysts followed by autologus blood instillation, then an immobilization for seven to ten days.Two years follow-up was done for detection any recurrence.Results: Most of the patients were females,and the dorsal aspect of the wrist affected more than the volar one. Most of the patients presented mainly because of cosmetic reasons.Recurrence was the only complication encountered and involved 50% in those of group A and 20% in those of group B.Conclusion: Our technique of aspirating the wrist ganglions and instillating autologus blood is a simple,safe,and effective method for treating wrist ganglions.